Acoustic motion estimation and control for an unmanned underwater vehicle in a structured environment - Caccia, M.; Casalino, G.; Cristi, R.; Veruggio, G. (Pergamon, 1998)
The problem of identification and navigation, guidance and control in unmanned underwater vehicles (UUVs) is addressed in this paper. A task-function-based guidance system and an acoustic motion estimation module have been integrated with a conventional UUV autopilot within a two-layered hierarchical architecture for closed-loop control. Basic techniques to estimate the robot dynamics using the sensors mounted on the vehicle have been investigated. The proposed identification techniques and navigation, guidance and control (NGC) system have been tested on Roby2, a UUV developed at the Istituto Automazione Navale of the Italian C.N.R. The experimental set-up, as well as the modalities and results, are discussed. Programma Nazionale di Recerche in Antartide (PNRA)